Leveraging digital transformation platforms to strengthen market position in India’s textile industry - Hajar Fatorachian; Samritha Ramesh (Cogent Business & Management)
The global textile industry is undergoing rapid transformation driven by digital technologies, shifting consumer preferences, and evolving market dynamics. This study explores how digital platforms—particularly e-commerce, CRM systems, and digital marketing tools—enhance operational efficiency, customer engagement, and market positioning for textile wholesalers. Grounded in the Technology Acceptance Model (TAM), Diffusion of Innovations (DOI) Theory, and the Resource-Based View (RBV), the research identifies key drivers and barriers to digital adoption. A mixed-methods approach, incorporating focus groups, surveys, and industry reports, supports a comprehensive analysis. A case study of Company A demonstrates how digital tools can address sector-specific challenges, increase competitiveness, and support sustainable growth. Findings show CRM systems improve customer retention through personalised service, e-commerce reduces inefficiencies and broadens market reach, and digital marketing boosts brand visibility. By integrating behavioural, organisational, and strategic perspectives, this study offers actionable insights for textile wholesalers seeking to thrive in a digitally evolving economy.